Global review of rural community enterprises : the long and winding road to creating viable businesses, and potential shortcuts - Donovan, Jason; Stoian, Dietmar; Poole, Nigel (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), 2020)
Government and civil society organizations are faced with the considerable task of promoting broad-based economic growth among the rural poor without compromising the natural resource base, while at the same time increas-ing the sustainability of their actions. In this context, rural community enterprises (RCEs) are increasingly being advocated because of their perceived ability to combine, with varying degrees of success, economic objectives with environmental and social objectives, such as sustainable resource management, improved local safety nets, increased influence over political processes, and member education. Recent changes in the political, legal, and market environment in devel-oping regions offer possibilities for RCE development that simply did not exist before. Reduced barriers to trade, including tariffs, quantitative restrictions, and other barriers, provide conditions for enhanced export performance for both traditional and nontra-ditional products. Structural adjustment programs substantially reduced or eliminated state-backed marketing boards and production cooperatives, thus opening new spaces for RCEs in the commercializa-tion of agriculture and forest products. In addition, emerging segments and niches in agricultural and for-est product markets, such as organic, certified timber, and specialty fruits, provide incentives for new com-munity-based business endeavors as well as attract external investments for upgrading RCE operations.